The leading feature of Luqman Borikhan's storytelling (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article highlights the leading features of Luqman Borikhan's storytelling. The characters and emotions of the characters in his stories are highlighted.